Antibody response to anaerobic coccoid rods in Crohn's disease. Issue 10 (October 1986) - Bull, K; Matthews, N; Rhodes, J
Abstract : The IgG and IgM specific antibodies against a panel of 23 anaerobic gut bacteria were examined in Crohn's disease, ulcerative colitis, and healthy controls. Four of the organisms, Bifidobacterium bifidum, Coprococcus comes (ME46), Coprococcus comes (Sp4), and Eubacterium limosum gave abnormal antibody titres in Crohn's disease compared with those of controls. In Crohn's disease specific IgG antibodies to three of the organisms were low and the IgM antibodies were higher than those of controls. IgM antibodies were also raised in ulcerative colitis. Antigenic cross reactivity could be shown between some of these organisms. The possible clinical importance of these abnormal antibody responses to specific organisms is unexplained.